2003
DOI: 10.1152/ajpendo.00398.2002
|View full text |Cite
|
Sign up to set email alerts
|

Studies with GIP/Ins cells indicate secretion by gut K cells is KATPchannel independent

Abstract: K cells are a subpopulation of enteroendocrine cells that secrete glucose-dependent insulinotropic polypeptide (GIP), a hormone that promotes glucose homeostasis and obesity. Therefore, it is important to understand how GIP secretion is regulated. GIP-producing (GIP/Ins) cell lines secreted hormones in response to many GIP secretagogues except glucose. In contrast, glyceraldehyde and methyl pyruvate stimulated hormone release. Measurements of intracellular glucose 6-phosphate, fructose 1,6-bisphosphate, and py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 75 publications
3
24
0
2
Order By: Relevance
“…The results presented in Figures 1-5, coupled with published observations from our lab (Ramshur et al 2002;Wang et al 2003), indicate that EE cells that produce CGA, but not GIP, express Kir 6.2, IP3R-1, and IP3R-3. Therefore, studies were performed to define the pattern of IP3R expression in additional subpopulations of EE cells.…”
Section: Different Subtypes Of Ee Cells Express Unique Repertoires Ofsupporting
confidence: 76%
See 2 more Smart Citations
“…The results presented in Figures 1-5, coupled with published observations from our lab (Ramshur et al 2002;Wang et al 2003), indicate that EE cells that produce CGA, but not GIP, express Kir 6.2, IP3R-1, and IP3R-3. Therefore, studies were performed to define the pattern of IP3R expression in additional subpopulations of EE cells.…”
Section: Different Subtypes Of Ee Cells Express Unique Repertoires Ofsupporting
confidence: 76%
“…Surprisingly, hormone release from GIP-producing cell lines is independent of ATP-regulated potassium channels (Ramshur et al 2002). Consistent with this result, IHC studies revealed that GIP-producing EE cells in the mouse small intestine do not express detectable levels of inward rectifying potassium channel 6.1 (Kir 6.1) or inward rectifying potassium channel 6.2 (Kir 6.2) (Wang et al 2003). Therefore, ATP-regulated potassium channels are not major regulators of cell depolarization and subsequent calcium mobilization in GIPproducing EE cells in vivo.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…Taken together, the electrogenic response of the murine L-cell to glucose is similar to the stimulus secretion coupling events that occur during glucose-stimulated insulin secretion, but unlike the ␤-cell, the absence of GLUT2 mRNA expression in the murine L-cell suggests that glucose transport is primarily facilitated by sodium glucose transporters. Nonetheless, a recent report has indicated that the K ATP channel cannot be detected in the mouse L-cell in vivo (69) and K ATP null mice do not show alterations in circulating GLP-1 levels (70). Thus, the physiological importance of the findings made with the murine L-cell in vitro remain to be confirmed.…”
Section: Intracellular Signaling Pathways Regulating Glp-1 Secretionmentioning
confidence: 99%
“…G protein-coupled receptors have been implicated in fatty acid sensing (15,22,36), glucose sensing (19,30,33,38,42), and protein/amino acid sensing (3)(4). Interestingly, intestinal transporters may also provide a nutrient-sensing role in the enteroendocrine cell.…”
mentioning
confidence: 99%